Repetitions in interrupted speech production - Horga, Damir (Array, 2008)
The aim of the ivestigation was to find out the characteristics of repetitions in speech production. The IHR constituent (Interruption, hesitation, repetition) presents evidence from speech production indicating that speech production is not a perfect mechanism and shows the obstacles speakers must overcome on the level of performance, especially in the motor programme or in planning.